2016
DOI: 10.1016/j.pupt.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of adjunctive tacrolimus in connective tissue disease-interstitial lung disease

Abstract: We evaluated the safety and effectiveness of adjunctive tacrolimus therapy with conventional immunosuppression in patients with severe connective tissue disease-related interstitial lung disease (CTD-ILD). We included patients from our interstitial lung disease (ILD) registry with CTD-ILD, in whom tacrolimus was added to corticosteroids and an additional immunosuppressive agent. Demographic data, clinical features, lung function, radiographic images, and pathologic findings were reviewed. Effectiveness was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…No study has demonstrated the superiority of a particular agent, so the choice of therapy is guided by practitioner comfort and a careful assessment of potential risks of therapy in an individual patient. Our practice is to initiate prednisone and azathioprine or mycophenolate mofetil in patients with anti-synthetase syndrome related ILD, with the addition of tacrolimus for rapid disease control in more severe ILD (50). In the setting of anti-synthetase syndrome, we use rituximab for patients with severe progressive and/or refractory ILD and have used cyclophosphamide in ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No study has demonstrated the superiority of a particular agent, so the choice of therapy is guided by practitioner comfort and a careful assessment of potential risks of therapy in an individual patient. Our practice is to initiate prednisone and azathioprine or mycophenolate mofetil in patients with anti-synthetase syndrome related ILD, with the addition of tacrolimus for rapid disease control in more severe ILD (50). In the setting of anti-synthetase syndrome, we use rituximab for patients with severe progressive and/or refractory ILD and have used cyclophosphamide in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these patients had anti-Jo-1 and two had anti-SRP autoantibodies. Since that time, numerous case reports and studies have suggested the efficacy of tacrolimus in patients with CTD and IIM related ILD (49), even as add-on therapy in combination with corticosteroids and an additional immunosuppressive agent (50). A 2005 case series specifically studied tacrolimus efficacy in 15 patients with anti-synthetase syndrome-ILD.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Mejia and colleagues recently demonstrated that all patients with ILD and a circulating tRNA synthetase antibody who failed to meet criteria for dermatomyositis subsequently met IPAF criteria and that survival was similar between the two groups. 45 Over one third of patients included in the IPAF cohort characterized by Chartrand and colleagues had a positive tRNA synthetase antibody, which given the proclivity of this group to respond to immunosuppression 46–48 , may explain the low mortality in this group compared to other IPAF cohorts.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…48-50 Polymorphisms within cytochrome p450 genes CYP3A5 and CYP3A5 have been shown to influence the bioavailability of tacrolimus. 51 Absorption of tacrolimus may also be influenced by the presence of polymorphisms within the MDR1 gene, which encodes a cellular efflux pump protein.…”
Section: Drug-specific Pharmacogenetic Biomarkersmentioning
confidence: 99%